Civic Participation Among Young People in Chile: An Association Analysis in Times of Covid-19 - Macias-Inzunza, L (UNIV SAO PAOLO, 2025)
Objective: To analyze the association between sociodemographic and socio-health factors on the civic participation of young people in Chile. Method: A cross-sectional study using the Tenth National Youth Survey. Descriptive statistics and models were used to examine associations between sociodemographic, socio-health, social participation, and sociopolitical variables in Chile. Results: Female sex and education levels indicated greater political participation. Being single, not being heads of household, being happy, having a positive outlook on their future, being satisfied with their finances, health, leisure time, having time available to spend with friends and family, and the country s characteristic democracy showed significant associations. No identification with specific political sectors, interest in political matters, and self-identification as not actively participating in politics had significant associations. Conclusion: Young people are essential for building future citizenship. Their unique characteristics must be strengthened through effective citizen participation strategies, mediated by education that fosters awareness of their own value as individuals who impact public policy.